Analisis Kesalahan Berbahasa dalam Podcast Deddy Corbuzier dengan Nadiem Makarim sebagai Media Pembelajaran Menulis Teks Argumentasi - Nafla Puteri Adely; Syifa Arulina; Syahrul Ramadhan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research discusses the analysis of language errors in Deddy Corbuzier's podcast with Nadiem Makarim as a learning medium for writing argumentative texts. This research aims to find out mistakes to become a tool in improving students' abilities in writing argumentative texts. The method used is a qualitative approach, this research uses descriptive methods and content analysis to analyze podcasts. The results of this research show that there are various language errors, such as grammar, word choice or diction, and sentence structure. By paying attention to these mistakes, students can improve the quality of oral and written arguments.